A Test to Measure the Knowledge of Farmers about Rapeseed Mustard Cultivation. (Indian Journal of Extension Education, 2016)
A study was conducted to develop a test for measuring the knowledge of the farmers about different production recommendations of the rapeseed mustard crop as it is one of the important oilseed crops grown in the country. Production and productivity of rapeseed mustard is low at national level as well as in the state of J&K.Lack of proper knowledge about production recommendation may be one of the main reasons and in this direction an attempt was made to develop a test. The test consists of twenty items with reliability coefficient .93.